Materials, Energy and Environment Engineering : Select Proceedings of ICACE 2015 - Mohan B., Raj; Srinikethan, G.; Meikap, Bhim Charan (Springer Singapore : Imprint: Springer, 2017)
This edited volume comprises the proceedings of ICACE-2015. In the recent past Chemical Engineering as a discipline has been diversifying into several frontier areas and this volume addresses the advances in core Chemical Engineering as well as allied fields. The contents of this volume focus on energy and environmental applications of chemical engineering research and on materials science aspects of chemical engineering. This book will be useful to researchers, students, and professionals, particularly those working on interdisciplinary applications of Chemical Engineering problems. .
Keywords: Materials science.; Catalysis.; Engineering -- Materials.; Environmental engineering.; Biotechnology.; Biomaterials.; elektronické knihy; electronic books